Fine Resolution Analysis of Microbial Communities Provides Insights Into the Variability of Cocoa Bean Fermentation - Pacheco-Montealegre, Mauricio Edilberto; Dávila-Mora, Lizeth Lorena; Botero-Rute, Lina Marcela; Reyes, Alejandro; Caro-Quintero, Alejandro (Frontiers in Microbiology, 2020)
Cocoa bean fermentation is an important microbial process, where most metabolites that affect chocolate quality and aroma are generated. Production of reproducible high-quality beans is a major challenge because most fermentations occur in open containers with a lack of variable control. Here we present a study that aims to identify the effect of farm protocols, climate, and bean mass exposure, in the dynamics and composition of microbial communities. Using high-throughput sequencing of molecular markers for bacteria and yeasts, complemented with culture-based methods, we evaluated the microbial diversity and dynamics associated to spontaneous cocoa fermentation in two distinct agro-ecological zones in Colombia. The bacterial communities were classified at two levels of evolutionary relationship, at a coarse resolution (OTU-level) and at a finer resolution (oligotype-level). A total of six bacterial OTUs were present in both farms, following a microbial succession that starts with the Enterobacteraceae family (one OTU), transitioning to the Lactobacillaceae family (three OTUs) and finishing with Acetobacteraceae family (two OTUs). When undesirable practices were done, OTUs were observed at unexpected moments during the fermentation. At a finer taxonomic resolution, 48 oligotypes were identified, with 46 present in both farms. These oligotypes have different patterns of prevalence. In the case of Lactobacillaceae a high evenness was observed among oligotypes. In contrast, for Enterobacteraceae and Acetobacteraceae a high dominance of one or two oligotypes was observed, these oligotypes were the same for both farms, despite geographic location and season of sampling. When the overall fermentations were compared using correlations matrices of oligotypes abundance, they show a clear clustering by farm, suggesting that farm protocols generate a unique fingerprint in the dynamics and interactions of the microbial communities. The comparison between the upper and middle layers of the bean mass showed that environmental exposure affects the paces at which ecological successions occur, and therefore, is an important source of cocoa quality heterogeneity. In conclusion, the results presented here showed that the dynamics of microbial fermentation can be used to identify the sources of variability and evidence the need for better fermentation technologies that favor the production of reproducible high-quality cocoa beans.